2009
DOI: 10.1021/ja901407j
|View full text |Cite
|
Sign up to set email alerts
|

NTA Directed Protein Nanopatterning on DNA Origami Nanoconstructs

Abstract: Precisely patterning proteins and other molecules at the nanoscale is crucial to future biosensing and optoelectronic applications. One- and two-dimensional DNA nanoconstructs have proven to be useful scaffolds for nanopatterning. This paper demonstrates the application of nitrilotriacetic acid (NTA) forming chelate complexes to localize histidine (His) tagged proteins via Ni(2+) ions onto DNA based structures. Particularly, enhanced green fluorescent protein (EGFP) was directed to specific surface locations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(108 citation statements)
references
References 17 publications
2
103
0
3
Order By: Relevance
“…[18] Recent advances in the origami technique [19] will enable our concept to be extended to three dimensions and to super-resolution techniques requiring photoswitchable fluorescent proteins. [20] Single-molecule methods can thus cover the full critical length scale from a few nanometers using fluorescenceresonance energy transfer (FRET) to the length scales of conventional optical microscopy. Such advances are also crucial for the study of dynamic processes such as diffusive or directed transport occurring on DNA-based nanostructures.…”
Section: 4) Nm (Seementioning
confidence: 99%
“…[18] Recent advances in the origami technique [19] will enable our concept to be extended to three dimensions and to super-resolution techniques requiring photoswitchable fluorescent proteins. [20] Single-molecule methods can thus cover the full critical length scale from a few nanometers using fluorescenceresonance energy transfer (FRET) to the length scales of conventional optical microscopy. Such advances are also crucial for the study of dynamic processes such as diffusive or directed transport occurring on DNA-based nanostructures.…”
Section: 4) Nm (Seementioning
confidence: 99%
“…Recently, interests have grown into areas such as elastocapillarity [7][8][9][10], contact-drop dispensing [11] with applications to scanning-probe lithography [12] and micromachined fountain-pen techniques [13]. Molecular-resolution surface patterning provides new opportunities for advanced tissue engineering [14], DNA self-assembled nanoconstructs [15], and highly sensitive protein chips [16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several materials have been found that enable the deposition of DNA origami structures while maintaining their structural integrity. These materials include mica [12], silicon dioxide [13], gold [14], and graphene oxide [2]. The ideal substrate surface must be atomically smooth to enable optimal patterning and imaging through atomic force microscopy (AFM) because the origami structures are very thin and conformal.…”
Section: Introductionmentioning
confidence: 99%